Dywersyfikacja szansą rozwoju indywidualnych gospodarstw rolnych w globalnej gospodarce - Woźniak, Marian (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2008)
Rural areas are facing transformation related to changes in image of third millennium rural areas as well as non-beneficial socio-economic phenomenon which appears on the rural areas. Development of their, is not presently closely connected with food production but with production of high quality food and with necessity to develop effective non-agricultural entrepreneurship next to effective agriculture. More often rural development is an object of interpretation in aspect of its multifunctionality where agriculture is one of many others activities conducted by rural farms. The diversification belongs than to the main behavior strategies of active rural areas and farms which are identified not just with food suppliers. In the article there were pointed out theoretical problems of multifunctionality in rural areas development as well as importance of farm diversification for maintenance of rural areas liveliness. There were also presented opinions from Podkarpacie rural areas society regarding to the possibility of its development